3(6x+2)-18x=12 (y=6x+2, so you plug in 6x+2 into the y in 3y-18x=12)
18x+6-18x=12 (Then you distribute the 3 to the 6x and to the 2)
6=12 (Combine like terms 18x-18x)
There is no solution. Hope this helps and makes sense.
Answer:
x is 3
and
y is 3
Step-by-step explanation:
(2*3)+(3*3) = 15
6+9 = 15
To find A' they used the rule of multiplication, which is:
the derivative of a product of two terms is the first term times the derivative of the second term plus the second term times the derivative of the first.
To find b' they just isolated b'
Answer:
-7/15
Step-by-step explanation:
-4/5 translates to -12/15 and 1/3 translates to 5/15.
When you add -12/15+5/15 you get
-12+5/15 so you get -7/15